2002
DOI: 10.1074/jbc.m207353200
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional Control of the Expression and Function of Diacylglycerol Acyltransferase-1 in Mouse Adipocytes

Abstract: Acyl-CoA:diacylglycerol acyltransferase-1 (DGAT1) catalyzes the final step of triglyceride synthesis in mammalian cells. Data obtained from DGAT1-knockout mice have indicated that this enzyme plays an important role in energy homeostasis. We investigated the regulation of the expression and function of DGAT1 in mouse 3T3-L1 cell as a model for mammalian adipocytes. We demonstrated that the DGAT1 protein level increased by ϳ90-fold following differentiation of 3T3-L1 into mature adipocytes, a change that was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 58 publications
5
41
0
Order By: Relevance
“…Indeed, the DGAT1 inhibitor oleanolic acid (35) significantly decreased microsomal DGAT1 activity and, in parallel, inhibited the extent of triglyceride biosynthesis in PON2-deficient MPM. Previous studies indicated that DGAT1 is predominantly regulated posttranscriptionally (37)(38)(39)(40). Our results clearly suggest that in PON2-deficient macrophages, although DGAT1 mRNA and protein levels were similar to those observed in control MPM, DGAT1 is activated.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, the DGAT1 inhibitor oleanolic acid (35) significantly decreased microsomal DGAT1 activity and, in parallel, inhibited the extent of triglyceride biosynthesis in PON2-deficient MPM. Previous studies indicated that DGAT1 is predominantly regulated posttranscriptionally (37)(38)(39)(40). Our results clearly suggest that in PON2-deficient macrophages, although DGAT1 mRNA and protein levels were similar to those observed in control MPM, DGAT1 is activated.…”
Section: Discussionsupporting
confidence: 63%
“…Levels of DGAT1 and DGAT2 mRNA increase markedly during the differentiation of NIH 3T3-L1 fibroblasts into adipocytes, corresponding to a large increase in DGAT activity (22,36,87,88). These findings indicate a robust upregulation of DGAT1 and DGAT2 during adipogenesis and suggest the involvement of C/EBPa or PPARg, transcription factors that control the expression of many genes in adipogenesis.…”
Section: Regulation Of Dgat Enzymesmentioning
confidence: 64%
“…However, when this site was mutated in human DGAT1 (a T316F mutation) and expressed in cells, no effects on in vitro DGAT activity or TG synthesis were seen (88). Additional evidence that DGAT activity may be posttranscriptionally regulated comes from observations in 3T3-L1 adipocytes, in which levels of DGAT1 or DGAT2 mRNA are disproportionate to changes in DGAT activity during adipogensis (22,36,88). Allosteric regulation is found in the DGAT1-related ACAT enzymes (107) but has not been demonstrated for either DGAT.…”
Section: Regulation Of Dgat Enzymesmentioning
confidence: 99%
“…Smaller changes were observed with stable mtGPAT1 overexpression in CHO cells, where a 3.8-fold increase in mtGPAT specific activity resulted in a 16% increase in total labeled glycerolipids (25). Fatty acid entry into cellular lipids also increases with overexpression of other acyltransferases, such as AGPAT1 activity in 3T3-L1 adipocytes and C 2 C 12 myotubes (39), and DGAT-1 in 3T3-L1 adipocytes (51). The only exception to this pattern of increased fatty acid uptake is a study in which stable overexpression of DGAT-1 activity in SV40-transformed human lung fibroblasts caused a marked decrease in cell proliferation and thus phospholipid synthesis (4).…”
Section: Discussionmentioning
confidence: 99%